Intervention of PKC-θ as an immunosuppressive regimen - Sun, Zuoming (Frontiers in Immunology, 2012)
PKC-θ is selectively enriched in T cells and specifically translocates to immunological synapse where it mediates critical T cell receptor signals required for T cell activation, differentiation and survival. T cells deficient in PKC-θ are defective in their ability to differentiate into inflammatory effector cells that mediate actual immune responses whereas, their differentiation into regulatory T cells (Treg) that inhibits the inflammatory T cells is enhanced. Therefore, the manipulation of PKC-θ activity can shift the ratio between inflammatory effector T cells and inhibitory Tregs, to control T cell-mediated immune responses that are responsible for autoimmunity and allograft rejection. Indeed, PKC-θ deficient mice are resistant to the development of several Th2 and Th17-dependent autoimmune diseases and are defective in mounting alloimmune responses required for rejection of transplanted allografts and graft-versus-host disease (GVHD). Selective inhibition of PKC-θ is therefore considered as a potential treatment for prevention of autoimmune diseases and allograft rejection.